Pembuatan Prototype Aplikasi Pengenalan Logo Berbasis Android - Tanggo, Ferry; Andjarwirawan, Justinus; Gunawan, Ibnu (Jurnal Infra, 2014)
Today many manufacturers are competing to introduce their products. This triggers creativity in advertising. These ads are made in a variety of formats, ranging from print, video or any other media. But with the advent of various media formats of this ads, there is also a variety of constraints. One problem is that operating costs are also high enough to affect the price of the product is higher as well. The workings of this application is to scan the logo image objects and sent to the server for processing. The results of the process will be immediately sent back to the user of smartphones in the form of image information. Another function is to share information about the logos to others by using social media which connected with the internet. Based on the test results, the application can perform object recognition in the form of logos and displays related information. Accuracy of the normal scan success of 68.75%, accuracy in dim state of 0%, on a slope of 5 ° -30 ° by 60%, on the state of the logo is cut off by 20%, in landscape orientation by 40% and the small logo by 20%. Users can also add logos and information needed, and can also interact with other users through the comment feature.